Building the New Urbanism : Places, Professions, and Profits in the American Metropolitan Landscape. - Passell, Aaron (Taylor and Francis, 2013)
The New Urbanism is perhaps the most influential movement that has emerged in suburban design, planning, and development in recent decades. It proposes to reform conventional suburban development by ""building community."" Building the New Urbanism asks ""why new urbanism now?"" to provide the first in-depth sociological investigation of the emergence of this phenomenon. This volume situates the growth of New Urbanism in the history of urban and suburban policy and development. The book builds an account of the movement's founding and development, linking its progress to the ma.